F-term uplift in heterotic M-theory - Paccetti Correia, Filipe; Schmidt, Michael G. (Nuclear physics. B, Particle physics, 2010)
We investigate the viability of F-term uplift in heterotic M-theory. With this aim we explore a natural ingredient of heterotic compactifications, namely vector bundle moduli. It is shown that it is generically possible to obtain stable de Sitter vacua with broken supersymmetry provided the little Kähler potential and the prefactors of the non-perturbative superpotential are suitably tuned. An additional requirement is the existence of non-trivial gauge instantons both at the visible and hidden sectors. This is illustrated with analytical and numerical examples.
Available online 27 October 2009
Gesehen am 21.06.2023